A CHECKLIST ON THE MOTH DIVERSITY (LEPIDOPTERA: HETEROCERA) AT MADRAS CHRISTIAN COLLEGE CAMPUS, TAMBARAM EAST, CHENNAI - METILDA, S. MERCY; LIVINGSTONE, ANANTHI RACHEL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Moths are diverse group of insects belonging to the order Lepidoptera and suborder Heterocera. They are regarded as one of the indicators of a healthy environment. This study deals with the first checklist of moth species in Madras Christian College campus, Tambaram. The study was carried out from December 2018 to September 2019. In total, 32 species of moths were identified from 29 genera falling under 9 families. The Moths identified belonged to the families of Erebidae, Noctuidae, Crambidae, Sphingidae, Eupterotidae, Uraniidae, Saturniidae, Geometridae and Tineidae of which, family Erebidae was found to be the superior family. The results of this preliminary study sheds light on the unknown biodiversity of moth, which needs to be strengthened through comprehensive future surveys. The objective of this study is to document moth diversity in Madras Christian College, Tambaram.